2014
DOI: 10.1525/jer.2014.9.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Years of Fogarty-Funded Bioethics Training in Latin America and the Caribbean: Achievements and Challenges

Abstract: The landscape in research ethics has changed significantly in Latin America and the Caribbean over the past two decades. Research ethics has gone from being a largely foreign concept and unfamiliar practice to an integral and growing feature of regional health research systems. Four bioethics training programs have been funded by the Fogarty International Center (FIC) in this region in the past 12 years. Overall, they have contributed significantly to changing the face of research ethics through the creation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…The NIH/ FIC has funded bioethics training programs in Latin America from 2002 to 2014 (Saenz et al, 2014). Four scholars from Bolivia participated in those trainings; however, it was noted that trained scholars had insufficient support in their own regions or institutions to further research ethics education and discussions (Saenz et al, 2014). An important goal of the NIH/FIC educational initiative is that trainees apply their research ethics knowledge and skills to strengthen practices and policies in their institutions and regions.…”
Section: Background Of the Studysupporting
confidence: 57%
See 1 more Smart Citation
“…The NIH/ FIC has funded bioethics training programs in Latin America from 2002 to 2014 (Saenz et al, 2014). Four scholars from Bolivia participated in those trainings; however, it was noted that trained scholars had insufficient support in their own regions or institutions to further research ethics education and discussions (Saenz et al, 2014). An important goal of the NIH/FIC educational initiative is that trainees apply their research ethics knowledge and skills to strengthen practices and policies in their institutions and regions.…”
Section: Background Of the Studysupporting
confidence: 57%
“…The National Institutes of Health/ Fogarty International Center (NIH/FIC) International Research Ethics Education and Curriculum Development Award (R25) was identified as a good fit for the aims of the Bolivian-TUC partnership focused on improving resources and practices related to research ethics (National Institutes of Health, Fogarty International Center, 2015). The NIH/ FIC has funded bioethics training programs in Latin America from 2002 to 2014 (Saenz et al, 2014). Four scholars from Bolivia participated in those trainings; however, it was noted that trained scholars had insufficient support in their own regions or institutions to further research ethics education and discussions (Saenz et al, 2014).…”
Section: Background Of the Studymentioning
confidence: 99%
“…These include the Fogarty-funded efforts of Saenz et al 45 and an effort by the CITI program at the University of Miami to make teaching materials available in Spanish for use in Costa Rica. These include the Fogarty-funded efforts of Saenz et al 45 and an effort by the CITI program at the University of Miami to make teaching materials available in Spanish for use in Costa Rica.…”
Section: E R H E R H and Building Capacity To Support Human Research Prmentioning
confidence: 99%
“…In most Latin American countries, including Argentina, the majority of research ethics education grants come from the NIH Fogarty International Center's Program on Research Ethics Education and Curricular Development (Saenz et al 2014). As research training grants, such programs include instruction in the responsible conduct of research as part of their focus on ethics (Saenz et al 2014).…”
Section: Education For the Promotion Of Research Integrity In Argentimentioning
confidence: 99%